2017
DOI: 10.3389/fpubh.2017.00231
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Disclosure on Health and Related Outcomes in Human Immunodeficiency Virus-Infected Children: A Literature Review

Abstract: This review explores the association between pediatric human immunodeficiency virus (HIV) disclosure and health and related outcomes among children living with HIV. A multi-stage process was used to search for relevant articles on the ISI Web of Knowledge database. Fifteen articles met the inclusion criteria. Five major outcomes emerged from children’s knowledge of their HIV-seropositive status: physical/physiological outcomes; adherence to antiretroviral therapy; psychosocial outcomes; sexual and reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
2
27
3
Order By: Relevance
“…Many studies have reported on how HIV disclosure improves ALHIV clinical, immunological and virological outcomes as well as retention in care [28,32,33,51,52]. In COHADO, we found that HIV disclosure tend to reduce the odds of having a favorable 24-month outcome, though this was not significant.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Many studies have reported on how HIV disclosure improves ALHIV clinical, immunological and virological outcomes as well as retention in care [28,32,33,51,52]. In COHADO, we found that HIV disclosure tend to reduce the odds of having a favorable 24-month outcome, though this was not significant.…”
Section: Discussioncontrasting
confidence: 67%
“…Data suggested that an earlier full HIV-disclosure could improve ALHIV outcomes through improved ART adherence, retention in care and slower disease progression [28,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported on how HIV-disclosure improves ALHIV clinical, immunological and virological outcomes as well as retention in care [28,32,33,51,52]. In COHADO, we found that HIV-disclosure during COHADO tend to reduce the odds of having a favorable 24-month outcome, though this was not signi cant.…”
Section: Discussioncontrasting
confidence: 60%
“…In West-Africa, less than a third of APHIV knew their status in 2011 and the HIV-disclosure process often occurred late, after the WHO-recommended age of 12 years [30,31]. Data suggested that an earlier full HIV-disclosure could improve ALHIV outcomes through improved ART adherence, retention in care and slower disease progression [28,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that HIV status disclosure is associated with improved health among children and halted disease progression [ 8 ]. However, there are mixed views on the association between disclosure and treatment adherence.…”
Section: Introductionmentioning
confidence: 99%